Implementasi Monitoring Jaringan Berbasis Web Terintegrasi Cacti Menggunakan Notifikasi Telegram - Manda Sari; Titania Halim Putri; Carly Dosen; M. Diarmansyah Batubara (Query: Journal of Information Systems, 2020)
Improving the quality of services on the network must be implemented and run easily in every institution, school, home, or other place that uses a computer network as an important means. One appropriate way is to find out network disruptions that occur in a fast time period, so that the interference can be overcome without needing a long time. Knowing the disruption that occurs in a faster time period is not easy if done the old way, that is network users realize that the network is not connected and report it to the network technician. After receiving the report the damaged network will be repaired. With a web-based system that is integrated with cacti, it can monitor and provide information via telegram messages in real time. The technician will immediately fix the disruption that occurred before the report from the user, so that network disruptions that occur will not last long. Keywords : cacti, web, telegram, networking